Composite diaphragm, preparation method thereof and secondary battery

By using a composite separator in a lithium-ion battery, the separator consists of a base film and a crosslinked polymer coating, the problem of traditional separator being easily broken at high temperatures and being unable to prevent gas crosstalk, achieving improved high temperature stability and safety of the battery.

CN119601903AActive Publication Date: 2025-03-11广州融捷能源科技有限公司

Patent Information

Application Number
CN202411491828.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-03-11
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

Traditional lithium-ion battery separators are prone to rupture at high temperatures, and cannot effectively prevent gas crosstalk between the positive and negative electrodes, resulting in thermal runaway.

Method used

A composite separator is used, which includes a base film and a polymer coating, which consists of a crosslinked polymer formed by the first monomer and the second monomer by in-situ polymerization, and has a network structure that can crosslink reactions at high temperatures to form a dense crosslinked polymer network.

Benefits of technology

The composite separator has a high film breaking temperature at high temperatures, which can effectively block the gas crosstalk between the positive and negative electrodes, inhibit the occurrence of thermal runaway from the battery, and slow down its diffusion by chelating lithium ions, significantly improving the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601903A_ABST
    Figure CN119601903A_ABST
Patent Text Reader

Abstract

The invention discloses a composite diaphragm, a preparation method thereof and a secondary battery. The composite diaphragm comprises a base diaphragm, the polymer coating is arranged on at least one surface of the base membrane, and the polymer coating comprises a cross-linked polymer which is formed by in-situ polymerization of a first monomer and a second monomer and has a network structure; wherein the first monomer is a monomer at least comprising a carbon-carbon double bond and an ester functional group; the second monomer is a monomer at least comprising a carbon-carbon double bond and a carbonyl functional group. Compared with the prior art, the composite diaphragm disclosed by the invention is applied to the lithium ion battery, and when the battery is overheated or short-circuited and other abnormal conditions, the polymer coating forms a compact cross-linked polymer network, so that the defect that the traditional polyolefin substrate diaphragm is easy to break at high temperature is overcome, the occurrence of thermal runaway of the battery is effectively inhibited, and the service life of the battery is prolonged. The electrochemical reaction of the battery can be stopped, and the safety of the battery is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a composite diaphragm and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have been widely used in various electronic devices and electric vehicles due to their high energy density, long cycle life and environmental friendliness. In the context of the country's promotion of the development of new energy, as the quality of life improves, the market has increasingly stringent requirements for battery life and safety. However, as the entire industry pursues energy density and the capacity of a single battery, the entire industry's battery cells have transitioned from low capacity and low energy density to high capacity and high energy density, and the chemical system has shifted from low gram capacity graphite to high gram capacity silicon plus graphite system, thereby achieving high energy density. However, battery safety issues, especially thermal runaway, have become the main challenge for batteries with high energy density systems.

[0003] Thermal runaway of lithium-ion batteries is usually caused by various abuse conditions. Among them, gas crosstalk between the positive and negative electrodes is the key factor that causes intense heating inside the battery. When the temperature rises above the phase transition point of the positive and negative electrode materials, active oxygen and reducing gases diffuse with each other to generate a large amount of heat, causing thermal runaway of the battery.

[0004] As one of the four main materials of lithium-ion batteries, the separator plays the role of isolating the positive and negative electrodes from each other and conducting lithium ions. However, traditional separators have the defect of easily breaking at high temperatures, and cannot prevent gas crosstalk between the positive and negative electrodes and inhibit the occurrence of thermal runaway of lithium-ion batteries.

[0005] In view of the above-mentioned defects of the current diaphragms, it is indeed necessary to provide a technical solution to the above-mentioned problems. Summary of the invention

[0006] The purpose of the present invention is to provide a composite diaphragm that can inhibit the occurrence of thermal runaway of a battery and significantly improve the safety of the battery.

[0007] In order to achieve this object, the present invention provides the following scheme:

[0008] A composite diaphragm, comprising:

[0009] Basement membrane;

[0010] A polymer coating layer is disposed on at least one surface of the base film, wherein the polymer coating layer comprises a cross-linked polymer having a network structure formed by in-situ polymerization of a first monomer and a second monomer;

[0011] Wherein, the first monomer is a monomer including at least a carbon-carbon double bond and an ester functional group; the second monomer is a monomer including at least a carbon-carbon double bond and a carbonyl functional group.

[0012] Preferably, the first monomer is selected from at least one of the following monomers: methyl methacrylate, ethyl methacrylate, methyl acrylate, ethyl acrylate, n-propyl acrylate, n-propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, n-butyl acrylate, n-butyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, sec-butyl acrylate, sec-butyl methacrylate, amyl acrylate, amyl methacrylate, n-octyl acrylate, n-octyl methacrylate, isooctyl acrylate, isooctyl methacrylate, isononyl acrylate, and isononyl methacrylate.

[0013] Preferably, the molecular weight of the second monomer is 100-300; the second monomer is at least one of acrylic anhydride, methacrylic anhydride, phthalic anhydride, maleic anhydride and succinic anhydride.

[0014] Preferably, the mass ratio of the first monomer to the second monomer is (7-12):(0.5-1.5).

[0015] Preferably, the deep eutectic solvent comprises a cyano compound and a lithium salt, the cyano compound is selected from at least one of succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, acrylonitrile, methacrylonitrile, and benzyl cyanide; the lithium salt is selected from at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonate)imide, and tris(trifluoromethylsulfonate)methyllithium; the mass ratio of the cyano compound to the lithium salt is (15-25):(12-17).

[0016] Preferably, the base film is a composite film formed by one or more of polyethylene, polypropylene, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, polyphenylene sulfide and polyethylene naphthalate; the porosity of the base film is 20-50%, and the air permeability of the base film is 30-400sec / 100cc.

[0017] Preferably, the thickness ratio of the base film and the polymer coating is (3-20):(1-5); the thickness of the base film is 3-20 μm; the thickness of the polymer coating is 1-5 μm.

[0018] Preferably, the initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate.

[0019] The present invention also provides a method for preparing a composite diaphragm, comprising the following steps:

[0020] Step 1: Mix the cyano compound and the lithium salt to prepare a deep eutectic solvent;

[0021] Step 2: adding the first monomer and the second monomer to the deep eutectic solvent, stirring for 20 to 40 minutes, stirring evenly to obtain a mixed solution; adding 0.4 to 0.6 wt % of an initiator, stirring for 10 to 20 minutes, mixing evenly to obtain a polymer coating slurry;

[0022] Step 2: coating the polymer coating slurry on at least one surface of the base film, and drying at 55-65° C. to obtain a composite diaphragm.

[0023] Preferably, in step 1, the solid content of the polymer coating slurry is 50% to 70%.

[0024] The present invention also provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte, a battery shell and the above-mentioned composite diaphragm.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: when the composite diaphragm of the present invention is used in a lithium-ion battery, when the battery is overheated or short-circuited, an in-situ cross-linking polymerization reaction occurs in the polymer coating to form a dense cross-linked polymer network; the cross-linked polymer network is resistant to high temperatures and has a high film rupture temperature, overcoming the defect that traditional polyolefin-based diaphragms are prone to film rupture at high temperatures; it can also have a certain adsorption effect on the active gas generated by the overheated battery cell, blocking the gas crosstalk between the positive and negative electrodes, and effectively inhibiting the occurrence of thermal runaway of the battery; the rich polar groups in the cross-linked polymer network can also effectively chelate lithium ions, slowing down the diffusion of lithium ions, thereby stopping the electrochemical reaction of the battery, and significantly improving the safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A schematic diagram of a composite diaphragm structure according to an embodiment of the present invention;

[0027] Figure 2 The thermal runaway test diagram of the lithium-ion battery of Example 1 and Comparative Example 9.

[0028] Among them, 1. base film; 2. polymer coating. DETAILED DESCRIPTION

[0029] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] According to a first aspect of the present invention, there is provided a composite diaphragm, comprising:

[0031] Basement membrane 1;

[0032] A polymer coating 2 is disposed on at least one surface of the base film 1, wherein the polymer coating 2 comprises a polymer having a network structure formed by in-situ polymerization of a first monomer and a second monomer;

[0033] Wherein, the first monomer is a monomer including at least a carbon-carbon double bond and an ester functional group; the second monomer is a monomer including at least a carbon-carbon double bond and a carbonyl functional group.

[0034] When the composite diaphragm is used in a lithium-ion battery, when the battery encounters abnormal situations such as overheating or short circuit, the polymer coating 2 undergoes a cross-linking polymerization reaction under high temperature conditions. The cross-linked polymer network is resistant to high temperatures and has a high film rupture temperature, overcoming the defect that traditional polyolefin-based diaphragms are prone to film rupture at high temperatures. It can also have a certain adsorption effect on the active gas generated by the overheated battery cell, blocking the gas crosstalk between the positive and negative electrodes, and effectively inhibiting the occurrence of thermal runaway of the battery. The rich polar groups (ester groups: -COO-) in the cross-linked polymer network can also effectively chelate lithium ions and slow down the diffusion of lithium ions, thereby stopping the electrochemical reaction of the battery and significantly improving the safety of the battery.

[0035] According to one embodiment of the present invention, the mass ratio of the first monomer to the second monomer is (7-12):(0.5-1.5); for example, it can be 7:1, 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1, 10:1, 10.5:1, 11:1, 11.5:1, 12:1, 7:0.5, 7.5:0.5, 8:0.5, 8.5:0.5 The mass ratio of the first monomer to the second monomer should be within this range. If the first monomer is too much, it will be difficult to achieve the in-situ polymer thermal induced cross-linking chemical reaction. If the first monomer is too little, it will be difficult to form a polymer coating.

[0036] In one embodiment of the present invention, the first monomer is selected from at least one of the following monomers: methyl methacrylate, ethyl methacrylate, methyl acrylate, ethyl acrylate, n-propyl acrylate, n-propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, n-butyl acrylate, n-butyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, sec-butyl acrylate, sec-butyl methacrylate, amyl acrylate, amyl methacrylate, n-octyl acrylate, n-octyl methacrylate, isooctyl acrylate, isooctyl methacrylate, isononyl acrylate, isononyl methacrylate. Further preferably, the first monomer is methyl methacrylate, with a molecular weight of 110.116, which is a highly active monomer with a wide electrochemical window and has good compatibility with high-voltage metal oxide cathode materials. Acrylic anhydride is an organic compound containing a large number of active unsaturated double bonds, and is a key component for realizing the in-situ polymer thermally induced cross-linking chemical reaction.

[0037] In one embodiment of the present invention, the molecular weight of the second monomer is 100-300, for example, it can be 100, 150, 200, 250, 300; when the monomer is used for polymerization, small molecular weight monomers are mostly used for ease of polymerization, while large molecular weight monomers are not easy to polymerize; the second monomer is at least one of acrylic anhydride, phthalic anhydride, maleic anhydride, and succinic anhydride.

[0038] In one embodiment of the present invention, the base film 1 is a composite film formed by one or more of polyethylene, polypropylene, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, polyphenylene sulfide and polyethylene naphthalate; the porosity of the base film 1 is 20-50%, for example, it can be 20%, 25%, 30%, 35%, 40%, 45%, 50%; the polyolefin base film 1 itself has good thermal stability, and the appropriate porosity helps to further improve its thermal stability. In abnormal conditions such as battery overheating or short circuit, the electrolyte in the pores can absorb part of the heat and slow down the temperature rise, thereby reducing the risk of thermal runaway of the battery.

[0039] The air permeability of the base film 1 is 30-400sec / 100cc. The polyolefin base film 1 with good air permeability can quickly release heat through the air permeable channel when the battery is overheated, thereby reducing the temperature inside the battery, which helps prevent thermal runaway and fire risks caused by overheating of the battery.

[0040] In one embodiment of the present invention, the thickness ratio of the base film 1 and the polymer coating 2 is (3-20): (1-5); the thickness of the base film 1 is 3-20 μm, for example, it can be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 20 μm; the polyolefin base film 1 with moderate thickness can reduce the dead space inside the battery, so that more active substances can be encapsulated in the battery, thereby improving the energy density of the battery, and can also reduce the mechanical stress of the battery during charging and discharging, thereby reducing the risk of damage to the diaphragm.

[0041] The thickness of the polymer coating 2 is 1 to 5 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm. The polymer coating 2 should not be too thick or too thin. If it is too thick, it will affect the energy density of the battery. If it is too thin, the polymer coating 2 will not be able to suppress the occurrence of thermal runaway of the lithium-ion battery and improve the safety performance of the lithium-ion battery.

[0042] In one embodiment of the present invention, the initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate.

[0043] In one embodiment of the present invention, the polymer coating 2 further includes a deep eutectic solvent, the deep eutectic solvent includes a cyano compound and a lithium salt, the cyano compound is selected from at least one of succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, acrylonitrile, methacrylonitrile, and benzyl cyanide; the lithium salt is selected from at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonate)imide, and tris(trifluoromethylsulfonate)methyllithium; the mass ratio of the cyano compound to the lithium salt is (15-25): (12-1 7), for example, it can be 15:15, 16:15, 17:15, 18:15, 19:15, 20:15, 21:15, 22:15, 23:15, 24:15, 25:15, 15:12, 16:12, 17:12, 18:12, 19:12, 20:12, 21:12, 22:12, 23:12, 24:12, 25:12, 15:17, 16:17, 17:17, 18:17, 19:17, 20:17, 21:17, 22:17, 23:17, 24:17, 25:17. The deep eutectic solvent composed of a nitrile compound solvent and a lithium salt has thermal stability and electrochemical stability. Adding the deep eutectic solvent to the coating of the composite diaphragm improves the thermal stability and electrochemical stability of the composite diaphragm; it can also provide a reaction environment for the first monomer and the second monomer, preparing for the subsequent suppression of thermal runaway.

[0044] In one embodiment of the present invention, the lithium salt includes at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluoro(oxalatoborate), lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonate)imide and tris(trifluoromethanesulfonate)methyllithium.

[0045] According to the second aspect of the present invention, there is also provided a method for preparing a composite diaphragm, comprising the following steps:

[0046] Step 1: Mix the cyano compound and the lithium salt to prepare a deep eutectic solvent;

[0047] Step 2: Add the first monomer and the second monomer to the deep eutectic solvent, stir for 20 to 40 minutes, stir evenly, and obtain a mixed solution; add 0.4 to 0.6 wt % of an initiator, stir for 10 to 20 minutes, mix evenly, and obtain a polymer coating 2 slurry;

[0048] Step 3: Coat the polymer coating 2 slurry on at least one surface of the base film 1, and dry it at 55-65° C. to obtain a composite diaphragm.

[0049] According to one embodiment of the present invention, in step one, the solid content of the polymer coating 2 slurry is 50% to 70%, for example, it can be 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, or 70%.

[0050] In a third aspect of the present invention, a secondary battery is provided, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte, a battery casing and the above-mentioned composite separator.

[0051] The positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer coated on at least one surface of the positive electrode current collector. The positive electrode active material layer may include but is not limited to a layered oxide positive electrode material, a spinel structure positive electrode material, an olivine structure positive electrode material, and a polyanion positive electrode material; the layered oxide positive electrode material comprises lithium nickel oxide (such as lithium nickel oxide), lithium cobalt oxide (such as lithium cobalt oxide LiCoO 2 ), nickel cobalt manganese oxide (such as NCM), nickel cobalt aluminum oxide (such as NCA), etc.; the spinel structure positive electrode material includes lithium manganese oxide (LiMn 2 O 4 ); the olivine structure positive electrode material includes lithium iron phosphate (LiFePO 4 ); The polyanionic positive electrode material includes phosphate and sulfate.

[0052] The positive electrode current collector can be any material suitable for use as a positive electrode current collector for lithium-ion batteries in the art, such as aluminum foil, copper foil, nickel foil, stainless steel or carbon material. The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector, and the negative electrode active material layer can include but is not limited to one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium.

[0053] The graphite may be selected from one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material may be selected from one or more of elemental silicon, silicon oxide compounds, silicon carbon composites and silicon alloys; the tin-based material may be selected from one or more of elemental tin, tin oxide compounds and tin alloys. The negative electrode current collector is usually a structure or part for collecting current. The negative electrode current collector may be any material suitable for use as a negative electrode current collector for lithium-ion batteries in the art. For example, the negative electrode current collector may include but is not limited to metal foil, and more specifically may include but is not limited to copper foil.

[0054] The secondary battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. The electrolyte lithium salt can be LiPF used in high temperature electrolytes. 6 and / or LiBOB; it can also be LiBF used in low temperature electrolytes 4 、LiBOB、LiPF 6 It can also be LiBF used in the overcharge-proof electrolyte 4 、LiBOB、LiPF 6 , LiTFSI; it can also be LiClO 4 、LiAsF 6 、LiCF 3 SO 3 、LiN(CF 3 SO 2 ) 2 At least one of the above. The organic solvent may be a cyclic carbonate, including PC, EC; it may also be a chain carbonate, including DFC, DMC, or EMC; it may also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to film-forming additives, conductive additives, flame retardant additives, overcharge prevention additives, and additives for controlling H in the electrolyte. 2 At least one of an additive for increasing the content of O and HF, an additive for improving low temperature performance, and a multifunctional additive.

[0055] The present invention will be further described below by means of specific examples.

[0056] Example 1

[0057] Preparation of composite diaphragm:

[0058] Step 1: mixing succinonitrile and lithium bis(trifluoromethylsulfonyl)imide in a mass ratio of 20:15 to obtain a deep eutectic solvent;

[0059] Step 2: adding methyl methacrylate and acrylic anhydride monomers in a mass ratio of 9:1, stirring for 30 minutes, stirring evenly, and obtaining a mixed solution; adding 0.5wt% of azobisisobutyronitrile, stirring for 15 minutes, mixing evenly, and obtaining a polymer coating 2 slurry;

[0060] Step 2: Coat the polymer coating 2 slurry on one surface of the base film 1 and dry it to obtain a composite diaphragm; wherein the base film 1 has a thickness of 10 μm and the polymer coating 2 has a thickness of 2 μm.

[0061] Preparation of lithium-ion batteries:

[0062] The negative electrode sheet, the positive electrode sheet and the above-mentioned separator are interlaced and wound and then packaged with an aluminum-plastic film to prepare a battery cell, which is placed in a battery shell, an electrolyte is added, and then sealed to obtain a lithium-ion battery. Among them, the active material of the negative electrode sheet is graphite; the active material of the positive electrode sheet is lithium iron phosphate; the electrolyte salt of the electrolyte is lithium hexafluorophosphate, and the solvent is ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 1:2:1, and the electrolyte concentration is 1 mol / L.

[0063] Table 1 shows the data of Examples 1 to 10 and Comparative Examples 1 to 8, and the rest is the same as Example 1 and will not be described again.

[0064] Table 1

[0065]

[0066]

[0067] Comparative Example 9

[0068] The difference from Example 1 is that the polymer coating 2 is changed into an alumina ceramic coating, wherein the thickness of the alumina ceramic coating is 10 μm.

[0069] The rest is the same as Example 1 and will not be described again here.

[0070] Comparative Example 10

[0071] Different from Example 1, the polymer coating 2 does not use a deep eutectic solvent, but uses succinonitrile as the solvent.

[0072] The rest is the same as Example 1 and will not be described again here.

[0073] Comparative Example 11

[0074] Different from Example 1, N-methylpyrrolidone is used as solvent in the polymer coating 2.

[0075] The rest is the same as Example 1 and will not be described again here.

[0076] Comparative Example 12

[0077] Different from Example 1, the polymer coating 2 uses N-methylpyrrolidone and lithium bis(trifluoromethylsulfonyl)imide mixed in a mass ratio of 20:15 as a solvent.

[0078] The rest is the same as Example 1 and will not be described again here.

[0079] Performance Test:

[0080] The membrane rupture temperature test was performed on the diaphragms of Examples 1 to 10 and Comparative Examples 1 to 12. The test results are shown in Table 2.

[0081] The lithium ion batteries of Examples 1 to 10 and Comparative Examples 1 to 12 were subjected to thermal runaway temperature tests, and the test results are shown in Table 2;

[0082] The lithium ion batteries of Example 1 and Comparative Example 9 were subjected to thermal runaway temperature tests. The test results are shown in Figure 1 .

[0083] Table 2

[0084]

[0085]

[0086] As shown in Table 2 and Figure 2 From the thermal runaway test data shown, it can be seen that the battery of Comparative Example 9 has experienced serious thermal runaway behavior when the temperature rises to 150°C, while the composite membranes of Examples 1 to 10 still do not experience thermal runaway behavior even at a high temperature of 250°C, indicating that when the composite membrane of the present invention is used in a lithium-ion battery, when the battery is overheated, the polymer coating 2 undergoes an in-situ polymerization reaction under high temperature conditions to form a dense cross-linked polymer network; the cross-linked polymer network can adsorb active gases, block gas crosstalk between the positive and negative electrodes, and effectively inhibit the occurrence of thermal runaway of the battery; the rich polar groups in the cross-linked polymer network can also effectively chelate lithium ions, slow down the diffusion of lithium ions, thereby stopping the electrochemical reaction of the battery, and significantly improving the safety of the battery.

[0087] By comparing the experimental data of Example 1 with those of Comparative Examples 1-2, it can be seen that the data of Example 1 is better than those of Comparative Examples 1-2, indicating that a mass ratio of the first monomer to the second monomer that is too large or too small will make it difficult to achieve an in-situ polymer thermally induced cross-linking chemical reaction or to form a polymer coating.

[0088] By comparing the experimental data of Example 1 and Comparative Examples 3-4, it can be seen that the data of Example 1 is better than those of Comparative Examples 3-4, indicating that when only the first monomer or only the second monomer is present, the polymer coating 2 cannot undergo in-situ polymerization reaction, the coating performance is poor, and the effect of improving the safety performance of the lithium-ion battery is not achieved.

[0089] By comparing the experimental data of Example 1 and Comparative Examples 5 to 6, it can be seen that if the thickness of the polymer coating 2 is too thick or too thin, although it can optimize the thermal runaway data of the composite diaphragm to a certain extent, too thick a thickness of the polymer coating 2 still has an impact on the thermal runaway data and also affects the energy density of the battery; if it is too thin, the polymer coating 2 cannot achieve the purpose of suppressing the occurrence of thermal runaway of the lithium-ion battery and improving the safety performance of the lithium-ion battery.

[0090] By comparing the experimental data of Example 1 and Comparative Examples 7 to 8, it can be seen that if the mass ratio of the initiator is too high or too low, although the thermal runaway data of the composite diaphragm can be optimized to a certain extent, too much initiator will waste initiator materials, increase costs, and have a negative impact on the thermal runaway data; and if the initiator is too little, the polymer coating 2 formed will be incomplete, resulting in poor thermal runaway data, and the purpose of improving the safety performance of the lithium-ion battery cannot be achieved.

[0091] By comparing the experimental data of Example 1 and Comparative Examples 10 to 12, it can be seen that when the polymer coating 2 does not have a deep eutectic solvent, the first monomer and the second monomer cannot achieve an in-situ polymer thermally induced cross-linking chemical reaction, and the coating performance is poor. Subsequently, it is also impossible to suppress the occurrence of thermal runaway of the lithium-ion battery, let alone improve the safety performance of the lithium-ion battery.

[0092] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A composite diaphragm, characterized in that: include: Basement membrane; A polymer coating layer is disposed on at least one surface of the base film, wherein the polymer coating layer comprises a cross-linked polymer having a network structure formed by in-situ polymerization of a first monomer and a second monomer; Wherein, the first monomer is a monomer including at least a carbon-carbon double bond and an ester functional group; the second monomer is a monomer including at least a carbon-carbon double bond and a carbonyl functional group.

2. The composite diaphragm according to claim 1, characterized in that: The first monomer is selected from at least one of the following monomers: methyl methacrylate, ethyl methacrylate, methyl acrylate, ethyl acrylate, n-propyl acrylate, n-propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, n-butyl acrylate, n-butyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, sec-butyl acrylate, sec-butyl methacrylate, amyl acrylate, amyl methacrylate, n-octyl acrylate, n-octyl methacrylate, isooctyl acrylate, isooctyl methacrylate, isononyl acrylate, and isononyl methacrylate.

3. The composite diaphragm according to claim 1, characterized in that: The molecular weight of the second monomer is 100-300; the second monomer is at least one of acrylic anhydride, methacrylic anhydride, phthalic anhydride, maleic anhydride and succinic anhydride.

4. The composite diaphragm according to claim 1, characterized in that: The mass ratio of the first monomer to the second monomer is (7-12):(0.5-1.5).

5. The composite diaphragm according to claim 1, characterized in that: It also includes a deep eutectic solvent, which includes a cyano compound and a lithium salt, wherein the cyano compound is selected from at least one of succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, acrylonitrile, methacrylonitrile, and benzyl cyanide; the lithium salt is selected from at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonate)imide, and tris(trifluoromethylsulfonate)methyllithium; and the mass ratio of the cyano compound to the lithium salt is (15-25):(12-17).

6. The composite diaphragm according to claim 1 or 5, characterized in that: The invention also comprises an initiator, which is at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate.

7. The composite diaphragm according to claim 1, characterized in that: The base film is a composite film formed by one or more of polyethylene, polypropylene, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, polyphenylene sulfide and polyethylene naphthalate; the porosity of the base film is 20-50%, and the air permeability of the base film is 30-400sec / 100cc.

8. The composite diaphragm according to claim 1, characterized in that: The thickness ratio of the base film and the polymer coating is (3-20):(1-5); the thickness of the base film is 3-20 μm; the thickness of the polymer coating is 1-5 μm.

9. A method for preparing a composite diaphragm, characterized in that: The following steps are involved: 1) Mixing a cyano compound and a lithium salt to prepare a deep eutectic solvent; 2) adding the first monomer and the second monomer to a deep eutectic solvent, stirring evenly to obtain a mixed solution; adding 0.4-0.6 wt % of an initiator to the mixed solution, stirring evenly to obtain a polymer coating slurry; 3) coating the polymer coating slurry on at least one surface of the base film, and drying at 55-65° C. to obtain the diaphragm.

10. A secondary battery comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, characterized in that: The diaphragm is the diaphragm according to any one of claims 1 to 8 or the diaphragm prepared by the preparation method of the diaphragm according to claim 9.

Citation Information

Patent Citations

  • Polymer as well as preparation method and application thereof

    CN113416270A

  • Modified diaphragm, battery and preparation method thereof

    CN118137070A

Cited By

  • Diaphragm and preparation method and application thereof

    CN120511432A

  • Battery diaphragm, preparation method thereof and lithium battery

    CN121529114A